Regulation of assimilatory nitrate reductase formation in Klebsiella aerogenes W70. - Bender, R A (1990)
Klebsiella aerogenes W70 could grow aerobically with nitrate or nitrite as the sole nitrogen source. The assimilatory nitrate reductase and nitrite reductase responsible for this ability required the presence of either nitrate or nitrite as an inducer, and both enzymes were repressed by ammonia. The repression by ammonia, which required the NTR (nitrogen regulatory) system (A. Macaluso, E. A. Best, and R. A. Bender, J. Bacteriol. 172:7249-7255, 1990), did not act solely at the level of inducer exclusion, since strains in which the expression of assimilatory nitrate reductase and nitrite reductase was was independent of the inducer were also susceptible to repression by ammonia. Insertion mutations in two distinct genes, neither of which affected the NTR system, resulted in the loss of both assimilatory nitrate reductase and nitrite reductase. One of these mutants reverted to the wild type, but the other yielded pseudorevertants at high frequency that were independent of inducer but still responded to ammonia repression.